Healing waters in Ancient Egypt: a connection between the sanatoria and the Houses of Life (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2024)
This contribution aims to investigate the function that healing waters played in the sanatoria and the Houses of Life – founding structures of the religious life of the Ancient Egyptians – starting from the assumption that water had a sacred and beneficial value, as the primordial element from which the world had its origin.  Fundamental, therefore, is the study of sanatoria, centres of worship, healing and medical speculation and, in particular, of the sanatorium of the temple complex of Hathor at Dendera, chosen as a case study to understand not only the functioning of the establishment itself, but also how healing waters constituted the centre of medical and magical practices of the time. Such practices were studied and learned by physicians in the so-called Houses of Life, structures variously interpreted in the course of the studies. In this discussion, therefore, an attempt will also be made to better understand the link between religion, medicine and magic, three pivotal aspects in the lives of the ancients.
Keywords: healing waters, sanatorium, House of Life, medicine, magic, religion